Integration of Constructivism in Arabic Language Learning at Islamic Higher Education: A Case Study at IAI Abuya Salek Sarolangun - Hadi Thoyib; Eko Parnandes; Prapti Octavia Ningsih (GHAITSA : Islamic Education Journal, 2026)
This study investigates the integration of constructivist principles in Arabic language learning at the Abuya Salek Sarolangun Islamic Institute (IAI Abuya Salek Sarolangun), Indonesia. The research addresses the gap between curriculum planning and classroom implementation in Arabic language instruction within Islamic higher education institutions. Unlike previous studies that mainly discuss constructivism conceptually, this study focuses on the discrepancy between Semester Learning Plans (RPS) and actual classroom practices. Using a qualitative case study approach, the research involved 25 students and two Arabic language lecturers selected purposively from a population of 60 students. Data were collected through participant observation, semi-structured interviews, and document analysis over a three-month period. The data were analyzed using thematic analysis, while data credibility was ensured through triangulation, member checking, and prolonged engagement. The findings indicate that Arabic language learning at IAI Abuya Salek Sarolangun has not fully integrated constructivist principles. Although lecturers occasionally apply interactive methods such as discussion and inquiry, classroom instruction remains predominantly lecturer-centered and relies heavily on lecturing and memorization. Learning activities have not optimally encouraged students’ critical thinking, collaboration, and independent knowledge construction. In addition, assessment practices still focus mainly on cognitive achievement through midterm and final examinations rather than authentic and process-oriented assessment. This study contributes to Arabic language pedagogy by proposing a contextual framework for strengthening constructivist learning implementation in Islamic higher education. The findings highlight the importance of curriculum alignment, lecturer professional development, and authentic assessment strategies to support meaningful and student-centered Arabic language learning.